PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN (EASE OF USE), KENYAMANAN (CONVENIENCE), KEPERCAYAAN (TRUST) DAN KETERSEDIAAN FITUR (FEATURE AVAILABILITY) TERHADAP MINAT NASABAH DALAM MENGGUNAKAN INTERNET BANKING KLIKBCA (STUDI KASUS PADA NASABAH PT BANK CENTRAL A - Harianto, Herry; Tri Setyo Mulyani, Hendarti; Oktalina, Gayatria (Jurnal Ilmiah Niaga Bisnis Elektronik, 2021)
This study aims to analyze and obtain evidence on the influence of perceptions of ease of use, convenience, trust and feature availability of intention to use internet banking KlikBCA. The results of this study are expected to contribute to the Bank in particular BCA in order to provide a service that is faster and easier for its customers. The object of this study is the BCA’s customers who use internet banking. Data used in this study are primary data, and data searching used questionnaires directly. The data used is primary data formed questionnaires that apply to BCA’s costumers who use KlikBCA in Pangkalpinang amount is 97 respondents and using method non probability sampling : purposive sampling. The results showed that perceptions ease of use, convenience, trust and feature availability has positive and significance impact on interest in using internet banking.